2011
DOI: 10.1017/s0032247411000374
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of AIS reception in Arctic regions from space by using a stratospheric balloon flight

Abstract: Due to the increased melting season in the arctic regions, especially in the seas surrounding Greenland, there has been an increased interest in utilizing these water ways, both as a efficient transport route and an attractive leisure destination. However, with heavier traffic comes an increased risk of accidents. Due to the immense size and poor infrastructure of Greenland, it is not feasible to deploy ground based ship monitoring stations throughout the Greenlandic coastline, thus the only feasible solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The satellites’ field of view is nearly 5,000 km in diameter, and they gather AIS transmissions from all vessels within that field of view (Marine Traffic, ). Although AIS pings in Arctic waters are not as accurate or frequent, due to the large distances between ships and satellites, and the absence of AIS antenna receivers in the Canadian Arctic, this is still the most efficient measure for tracking vessels (Larsen et al, ). The launch of new satellites from the two major AIS constellations, exactEarth and ORBCOMM, as well as the addition of new satellites such as the RADARSAT Constellation Mission (RCM) and the recent launch of M3MSat, will increase the density of the pings, allowing for better monitoring of vessel traffic patterns (Canadian Space Agency, ; exactEarth, ; Parsons, Youden, & Fowler, ; RCM, ).…”
Section: Methodsmentioning
confidence: 99%
“…The satellites’ field of view is nearly 5,000 km in diameter, and they gather AIS transmissions from all vessels within that field of view (Marine Traffic, ). Although AIS pings in Arctic waters are not as accurate or frequent, due to the large distances between ships and satellites, and the absence of AIS antenna receivers in the Canadian Arctic, this is still the most efficient measure for tracking vessels (Larsen et al, ). The launch of new satellites from the two major AIS constellations, exactEarth and ORBCOMM, as well as the addition of new satellites such as the RADARSAT Constellation Mission (RCM) and the recent launch of M3MSat, will increase the density of the pings, allowing for better monitoring of vessel traffic patterns (Canadian Space Agency, ; exactEarth, ; Parsons, Youden, & Fowler, ; RCM, ).…”
Section: Methodsmentioning
confidence: 99%
“…Numerous evaluations of S-AIS have been conducted. Statistics (Eriksen et al, 2010; Larsen et al, 2012) on received messages and extrapolations (Larsen et al, 2012) of how many messages have been missed, have been reported. A computer-based simulator was developed and used to predict ship/message probability of detection (Cervera et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Statistics (Eriksen et al, 2010;Larsen et al, 2012) on received messages and extrapolations (Larsen et al,942 A N N A -L I E S A S. L A P I N S K I A N D O T H E R S VOL. 69 2012) of how many messages have been missed, have been reported.…”
mentioning
confidence: 99%